Stock market reaction towards SPECT events using CAPM adjusted return - Nicholas Renaldo, Teddy Chandra,; Cadalora Putra, Lucky (Opción, 2019)
The aim of the research is to analyze the market reaction towards Tax Amnesty Policy. The indicators used in study are abnormal return and trading volume activity. Event study method is used to examine the market’s reaction and measure the differences before and after the announcement of the tax amnesty policy. The samples are all companies listed in LQ-45 sector. Abnormal return is calculated using CAPM Adjusted Return technique. The results showed that there are no significant differences in abnormal returns before and after all events. The trading volume activity also showed no significant difference before and after all events.